2017
DOI: 10.21767/2471-8041.100053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Triangular Fibrocartilage Complex Abnormalities among Asymptomatic Young Individuals Using Magnetic Resonance Imaging in A Tertiary Center in Saudi Arabia: A Cross-Sectional Study

Abstract: This study aims to detect and evaluate abnormalities and injuries of triangular fibrocartilage complex (TFCC) using 3.0 T high-resolution MRI. It also determines its efficacy among young asymptomatic individuals. This is a cross sectional exploratory study with a sample size of 30 (21 women and 9 men). None of the volunteers showed signs for previous wrist injuries. Details of TFCC morphology were determined using MRI images for dominant wrist. Analysis of locations for tear or degeneration or any characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Case presentation and brief overview of literature with regard to general, specific and practicable aspects to primary trauma-related surgical treatment including possible salvage options at the distal radioulnar joint Longstanding UPV is generally associated with secondary degenerative lesions of the triangular fibrocartilage due to it compression, and additionally, primary degenerative lesions of the triangular fibrocartilage with or without UPV and in the absence of any clinical symptoms are also well known but it mostly occur in elderly patients aged 60 years and older [43][44][45][46][47]. Hence, it cannot always be concluded that a lesion of the triangular cartilage, assessed by MRI and wrist arthroscopy, in a young patient with evident acute traumatic UPV in which the triangular cartilage is generally detached or disrupted could mainly be caused by a pre-existing non-traumatic degenerative lesion, or that a chronic ulnar-sided wrist pain in an elderly patient with evident longstanding UPV longer than 2 mm (Figures 4 and 5) is based on a lesion of the triangular cartilage that consequently would requires MRI and wrist arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Case presentation and brief overview of literature with regard to general, specific and practicable aspects to primary trauma-related surgical treatment including possible salvage options at the distal radioulnar joint Longstanding UPV is generally associated with secondary degenerative lesions of the triangular fibrocartilage due to it compression, and additionally, primary degenerative lesions of the triangular fibrocartilage with or without UPV and in the absence of any clinical symptoms are also well known but it mostly occur in elderly patients aged 60 years and older [43][44][45][46][47]. Hence, it cannot always be concluded that a lesion of the triangular cartilage, assessed by MRI and wrist arthroscopy, in a young patient with evident acute traumatic UPV in which the triangular cartilage is generally detached or disrupted could mainly be caused by a pre-existing non-traumatic degenerative lesion, or that a chronic ulnar-sided wrist pain in an elderly patient with evident longstanding UPV longer than 2 mm (Figures 4 and 5) is based on a lesion of the triangular cartilage that consequently would requires MRI and wrist arthroscopy.…”
Section: Discussionmentioning
confidence: 99%